2012
DOI: 10.1093/aje/kws156
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Self-reported Diabetes in the Atherosclerosis Risk in Communities Study

Abstract: The objective of this study was to assess the validity of prevalent and incident self-reported diabetes compared with multiple reference definitions and to assess the reliability (repeatability) of a self-reported diagnosis of diabetes. Data from 10,321 participants in the Atherosclerosis Risk in Communities (ARIC) Study who attended visit 4 (1996-1998) were analyzed. Prevalent self-reported diabetes was compared with reference definitions defined by fasting glucose and medication use obtained at visit 4. Inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
157
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 16 publications
(13 reference statements)
15
157
1
3
Order By: Relevance
“…Indeed, Bays et al reported that the prevalence of diabetes was similar when based solely on self-report in the SHIELD screening survey compared with clinical and laboratory corroboration of self-reports in NHANES (31). Schneider and colleagues also showed that self-reported diabetes was over 92% reliable and 83% sensitive (32). We were unable to differentiate between type 1 and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 60%
“…Indeed, Bays et al reported that the prevalence of diabetes was similar when based solely on self-report in the SHIELD screening survey compared with clinical and laboratory corroboration of self-reports in NHANES (31). Schneider and colleagues also showed that self-reported diabetes was over 92% reliable and 83% sensitive (32). We were unable to differentiate between type 1 and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 60%
“…Another limitation is the use of self-reports to evaluate diabetes mellitus, which may lead to an underestimation of the disease's prevalence, since some elderly individuals may be unaware of their diagnosis. In spite of this, in an investigation carried out on 10,321 individuals (average age = 63 years), use of selfreported diabetes had high validity and specificity in the identification of its prevalence and incidence, when compared with standard recommendations, based on fasting plasma glucose levels, glycosylated hemoglobin (HbA1c) and medication use 51 . The method used to classify race may also be considered a limitation, given the subjective and dynamic nature of this criterion based on self-reported skin color.…”
Section: Discussionmentioning
confidence: 96%
“…All the mentioned studies used medical records as reference standard. It should be noted, however, that the phrasing of questions and types of criterion standard affect the sensitivity and positive predictive value of questionnaires [27]. Furthermore, some publications have reported that the Sami people may be more inclined than non-Sami to underreporting diseases due to some cultural differences and/or language barriers (differential misclassification) [28].…”
Section: Discussionmentioning
confidence: 99%